2017
DOI: 10.11648/j.ab.20170501.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Energy of Consciousness (The Trivedi Effect<sup>®</sup>) on the Structural Properties and Isotopic Abundance Ratio of Magnesium Gluconate Using LC-MS and NMR Spectroscopy

Abstract: Abstract:Magnesium gluconate has the wide application for the prevention and treatment of hypomagnesemia. The objective of the current study was to investigate the effect of The Trivedi Effect ® -Energy of Consciousness Healing Treatment (Biofield Energy Healing Treatment) on magnesium gluconate for the change in the structural properties and isotopic abundance ratio (P M+1 /P M ) using LC-MS and NMR spectroscopy. Magnesium gluconate was divided into two parts -one part was control, and another part was treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Therefore, the researchers all over the world, paying attention to the improvement of the pharmaceutical and nutraceutical compounds. Similarly, it was experimentally observed that the Trivedi Effect ® (Biofield Energy Healing Treatment) has a huge impact on various properties of pharmaceutical/nutraceutical compounds [19][20][21][22]. The Trivedi Effect ® is a scientifically proven phenomenon in which a healer/expert can harness this intelligent energy and transfer it wherever on the planet via the possible mediation of neutrinos [23].…”
Section: Ntnf000586 4(3)2019mentioning
confidence: 99%
“…Therefore, the researchers all over the world, paying attention to the improvement of the pharmaceutical and nutraceutical compounds. Similarly, it was experimentally observed that the Trivedi Effect ® (Biofield Energy Healing Treatment) has a huge impact on various properties of pharmaceutical/nutraceutical compounds [19][20][21][22]. The Trivedi Effect ® is a scientifically proven phenomenon in which a healer/expert can harness this intelligent energy and transfer it wherever on the planet via the possible mediation of neutrinos [23].…”
Section: Ntnf000586 4(3)2019mentioning
confidence: 99%
“…(the Trivedi Effect ® ) has been considered these days as a novel approach due to its considerable impact on the physicochemical and thermal behaviour of various compounds [7][8][9]. The Trivedi Effect ® is considered as a scientifically proven phenomenon which involves the principle that a person can harness the inherently intelligent energy from its surroundings and transmit it in an object(s) (living/non-living) through the possible mediation of neutrinos [10].…”
Section: The Biofield Energy Healing Treatmentmentioning
confidence: 99%
“…Study of the physicochemical properties of a pharmaceutical product regarding its dissolution and absorption is crucial for the formulation. It was observed that the Biofield Energy Healing Treatment (the Trivedi Effect ® ) has the considerable impact on various properties such as particle size, surface area, and other chemical and thermal behaviour of pharmaceutical/nutraceutical [8][9][10][11]. The Trivedi Effect ® is a natural and scientifically proven phenomenon in which a person can harness this inherently intelligent energy and transmit it anywhere on the planet through the possible mediation of neutrinos [8].…”
Section: Introductionmentioning
confidence: 99%
“…The Trivedi Effect ® -Consciousness Energy Healing Treatment has been widely reported with astounding capability to alter the characteristic properties of the several non-living materials and living object(s), i.e. metals and ceramic, organic compounds, nutraceutical/pharmaceuticals, and crops [9][10][11][15][16][17][18][19][20][21][22][23]. The Consciousness Energy Healing Treatment has also enhanced the bioavailability of pharmaceutical/nutraceutical compounds [24][25][26].…”
Section: Introductionmentioning
confidence: 99%